Introductory quantum optics - Gerry, C. C. (Christopher C.) (Cambridge University Press, 2005)
This book provides an elementary introduction to quantum optics, the study of the quantum mechanical nature of light and its interaction with matter. It is designed for upper-level undergraduates taking courses in quantum optics who have already taken courses in quantum mechanics, and for first and second year graduate students.